PW 1000 Deaths by immersion in and around homes in canada, twenty-three years of epidemiology and failed policy: a built environment issue. (November 2018) - Barss, Peter; Hamilton, Jane; Dalke, Shelley; Olsen, Karlyn
Abstract : Background: National population-based data on home drownings are scarce. They represent 17% (1995/11280) of submersion fatalities in Canada. Objective: Assess circumstances of drownings in/around homes, i.e., activities, personal, equipment, environment. Methods: Using structured questionnaires, coroners' data were collected prospectively in 1991–2013 during national surveillance of water-related injury deaths. Population averaged 30 million. Findings: 11 915 deaths included 11 280 immersions with drowning and/or hypothermia, 584 trauma 39 other 12 unknown. 18% (n=1, 995) occurred at home and 5% (n=515) at cottages/cabins. Activities: Bathing accounted for 43%(n=864), aquatic 23%(n=466), falls into water 28%(n=565), other knowns 6%(n=111), unknown 2%(n=36). Personal factors: Victims were 60% male. 61% of females and 32% of males drowned in bathtubs. 32% of males drowned in swimming pools, 22% of females. Infants<1 year-old accounted for 3%(n=57) of deaths, toddlers 1–4 years-old 17%(n=344), 5–14 year-olds 5%(n=107), 15–24 year-olds 7%(n=140), 25–74 year-olds 51%(n=1014), and ≥75, 17%(333). 3% were indigenous peoples. Medical conditions included seizures 17%(n=353), mental disabilities 5%, depression 7%, alcoholism 10%, schizophrenia 2%, physical disabilities 5%, diabetes 5%, and acute medical condition such as cardiac 3%. For ≥15 years-olds, 29% were alcohol associated, 22% above 80 mg%, 5% below, 2% suspected, 48% zero; Illegal drugs 5%. 14% were non-swimmers, 3% weak. Environment: 77% (n=1567) involved person-made structures: bathtubs 56%(n=877), swimming pools 36% (n=557), hot tubs 8%(n=119), ornamental ponds 1%(n=14). Flatwater, i.e., lakes, ponds, reservoirs and dugouts accounted for 11%(n=228), moving water, i.e., rivers and streams 5%(n=96), oceans<1%(n=6). Supervision/accompaniment: For children 1–14 years old, 68% were alone, 22% with minors, and 10% with adults. Resuscitation: CPR and/or rescue breathing was done for 55%. Trends: There was a mean 87 deaths/year, 0.28/100, 000 population/year and no significant change. Conclusion and policy implications: Nearly all fatalities involved consumer products in built environments and should be avertable by design, eliminating or modifying pools and adult bathtubs. Alcohol and seizures were other modifiable hazards.